1997
DOI: 10.1007/s004600050111
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian integral transforms of unconventional functions: contracted basis functions appropriate to molecules and metallic clusters

Abstract: We report the development of new gaussian integral transforms one-electron functions. A straightforward recipe to generate gaussian contractions of these functions is introduced. The applications call into question the disseminated belief of the superiority of Slater type orbitals (STO) in molecular calculations. A first successful application of the Bessel K J (qr) function to a molecular system is presented. One of the integral transforms that yields the 0s function is used to generate contractions that have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several qualitative valence bond (VB) mechanisms for electron conduction in alkali metals have been proposed, [1][2][3][4][5][6][7][8][9][10] but except for a provisional study reported in ref 10, no quantitative VB studies of the process have been published. A number of ab initio VB studies of the electronic structures of lithium clusters have been published, 9,[11][12][13][14][15][16][17][18] and in ref 9, Lester and co-workers also give attention to conduction mechanisms in a qualitative manner. In this paper, we study aspects of two VB mechanisms for electron conduction along a linear chain of six and eight lithium atoms, arranged as Li A Li B Li C Li D Li E Li F and Li A Li B Li C Li D Li E Li F Li G Li H , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several qualitative valence bond (VB) mechanisms for electron conduction in alkali metals have been proposed, [1][2][3][4][5][6][7][8][9][10] but except for a provisional study reported in ref 10, no quantitative VB studies of the process have been published. A number of ab initio VB studies of the electronic structures of lithium clusters have been published, 9,[11][12][13][14][15][16][17][18] and in ref 9, Lester and co-workers also give attention to conduction mechanisms in a qualitative manner. In this paper, we study aspects of two VB mechanisms for electron conduction along a linear chain of six and eight lithium atoms, arranged as Li A Li B Li C Li D Li E Li F and Li A Li B Li C Li D Li E Li F Li G Li H , respectively.…”
Section: Introductionmentioning
confidence: 99%